Nowhere to Hide - Okoye, Ifeoma (Evans Brothers (Nigeria Publishers) Ltd, 2000)
Ral, the baby of Kolo family is an undergraduate in Kizito University. The sudden death of his older twin brother imposes on him the role of the first and only child of the Kolos. Would Ral be able to carry this burden?...
Keywords: Juvenile Fiction